Application of Time Recursive Processing for the Development of a Time/Phase Shifter - Perisic, D. M.; Bojovic, M. (Engineering, Technology & Applied Science Research, 2017)
This paper describes a powerful digital time and/or phase shifter of pulse rates, based on Time Recursive Processing. It can function either as a time shifter or as a phase shifter. The circuit can generate precise shifting for a pulse rate with a constant input period, but it is also capable to shift a pulse rate whose period is a ramp function. Besides that, the shifter can be used in tracking and prediction applications. The shifter is described by recursive equations as a linear discrete system. All mathematical analyses are made using the Z transform. Computer simulations are employed to prove the correctness of the mathematical analysis. The realization of the shifter is described and, to demonstrate the shifter functioning, actual oscilloscope screenshots are presented.